Deep-water polychaetes from a transect off Central Oregon. - Fauchald , Kristian; Hancock, Danil R. (Los Angeles, California Allan Hancock Foundation, 1981)
Monographs of the Allan Hancock Foundation; No.11 July 1981
Keywords: Polychaeta--Central Oregon